Marketing strategies of Polish companies on foreign markets - Grzegorczyk Wojciech (Management)
In the years 2017-2018 the Marketing Faculty of Łódź University conducted a research project “Marketing strategies of companies based in Łódź Voivodeship on foreign markets”. The aim of this text is to present the initial research findings strategies implemented by surveyed companies on foreign markets. The examined companies seldom attempted to conduct the foreign market research and the marketing strategy that they used was strictly related to the prevailing form of expansion into foreign markets, i.e. export. Both the product and the pricing policy were adapted to the specific character of the foreign market. Activities in the area of distribution were limited to indirect export and they were not initiated by the examined companies. The prevailing majority of companies used the Internet, trade fairs and exhibitions in their promotional activities. The intermediaries in the distribution channel were responsible for subsequent promotional activities. They involve marketing strategies typical for small and medium companies and their content depends on the intermediaries in the distribution channel on foreign markets.